The Pay Information Awareness Questionnaire (PIAQ): A Comprehensive Measure of Pay Transparency - Henn, Carolyn M.; Neck, Christopher B.; Houghton, Jeffery D. (Compensation and benefits review, 2025)
Pay transparency has drawn substantial attention from scholars in recent years, resulting in an expanding body of knowledge on this important topic. However, the literature has developed in a fragmented manner with an array of labels and conceptualizations across several largely disconnected dimensions. Pay transparency measurement scales have also emerged in a piecemeal fashion and lack cohesion in the operationalization of pay transparency dimensions. The current research develops a more cohesive and comprehensive multi-dimensional pay transparency framework and measurement scale. The paper reviews and integrates the pay transparency literature into a coherent, multi-dimensional framework founded on employee awareness perceptions of pay information rather than on objective organizational actions or employee behaviors. Following established scale development techniques, the present study creates and validates a multi-dimensional pay information awareness scale that may serve to facilitate future research on pay transparency. Implications are discussed, along with limitations and directions for future research.